GA document 123 :. (Tokyo : A.D.A. edita, 2013)
- Morphosis: Perot Museum of Nature and Science,Dallas, Texas, U.S.A.##- Morphosis: Museum of Fine Arts Houston, Houston, Texas, U.S.A.##- Morphosis: National Art Museum of China, Beijing, Beijing, China##- SANAA: Louvre-Lens, Lens, France##- Tod Williams Billie Tsien: Reva and David Logan Center for the Arts, University of Chicago, Chicago, Illinois, U.S.A.##- Jean Nouvel: Theater of Archipelago, Perpignan, Perpignan, France##- Steven Holl: Raffles City Chengdu - Sliced Porosity Block, Chengdu, China##- Zaha Hadid: Galaxy SOHO, Beijing, Beijing, China##- Zaha Hadid: Pierres-Vives, Montpellier, France##- Zaha Hadid: Eli & Edythe Broad Art Museum, East Lansing, Michigan, U.S.A.##-
boek